Comparing adventitious root-formation and graft-unification abilities in clones of Argania spinosa - Tzeela, Pann; Yechezkel, Sela; Serero, Ori; Eliyahu, Avi; Sherf, Sara; Manni, Yair; Doron-Faigenboim, Adi; Carmelli-Weissberg, Mira; Shaya, Felix; Dwivedi, Vikas; Sadot, Einat (Frontiers in Plant Science, 2022)
Argania spinosa trees have attracted attention in recent years due to their high resistance to extreme climate conditions. Initial domestication activities practiced in Morocco. Here we report on selection and vegetative propagation of A. spinosa trees grown in Israel. Trees yielding relatively high amounts of fruit were propagated by rooting of stem cuttings. High variability in rooting ability was found among the 30 clones selected. In-depth comparison of a difficult-to-root (ARS7) and easy-to-root (ARS1) clone revealed that the rooted cuttings of ARS7 have a lower survival rate than those of ARS1. In addition, histological analysis of the adventitious root primordia showed many abnormal fused primordia in ARS7. Hormone profiling revealed that while ARS1 accumulates more cytokinin, ARS7 accumulates more auxin, suggesting different auxin-to-cytokinin ratios underlying the different rooting capabilities. The hypothesized relationship between rooting and grafting abilities was addressed. Reciprocal grafting was performed with ARS1/ARS7 but no significant differences in the success of graft unification between the trees was detected. Accordingly, comparative RNA sequencing of the rooting and grafting zones showed more differentially expressed genes related to rooting than to grafting between the two trees. Clustering, KEGG and Venn analyses confirmed enrichment of genes related to auxin metabolism, transport and signaling, cytokinin metabolism and signaling, cell wall modification and cell division in both regions. In addition, the differential expression of some key genes in ARS1 vs. ARS7 rooting zones was revealed. Taken together, while both adventitious root-formation and graft-unification processes share response to wounding, cell reprogramming, cell division, cell differentiation and reconnection of the vasculature, there are similar, but also many different genes regulating the two processes. Therefore an individual genotype can have low rooting capacity but good graft-unification ability.